2018
DOI: 10.1128/aem.00106-18
|View full text |Cite
|
Sign up to set email alerts
|

A Standard Method To Inactivate Bacillus anthracis Spores to Sterility via Gamma Irradiation

Abstract: In 2015, a laboratory of the United States Department of Defense (DoD) inadvertently shipped preparations of gamma-irradiated spores of Bacillus anthracis that contained live spores. In response, a systematic evidence-based method for preparing, concentrating, irradiating, and verifying the inactivation of spore materials was developed. We demonstrate the consistency of spore preparations across multiple biological replicates and show that two different DoD institutions independently obtained comparable dose-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…For example high concentrations of irradiated dead spores (≥9 log 10 spores per ml) subsequently interfered with the recovery of any remaining live spores for spore populations that were not sufficiently irradiated because Alr is not inactivated during irradiation (Cote et al . ). The data herein indicate that the highest practical confidence for recovery of any live spores within an irradiated spore sample would include a preliminary incubation at 15–25°C, ≥24 h (or longer) in recovery medium.…”
Section: Discussionmentioning
confidence: 97%
“…For example high concentrations of irradiated dead spores (≥9 log 10 spores per ml) subsequently interfered with the recovery of any remaining live spores for spore populations that were not sufficiently irradiated because Alr is not inactivated during irradiation (Cote et al . ). The data herein indicate that the highest practical confidence for recovery of any live spores within an irradiated spore sample would include a preliminary incubation at 15–25°C, ≥24 h (or longer) in recovery medium.…”
Section: Discussionmentioning
confidence: 97%
“…No equivalent NHEJ system has been identified experimentally the B. cereus group strains investigated in the current study, although NHEJ-associated proteins (such as Ku-like proteins) have been identified by homology analysis. According to published research, NHEJ-mediated repair mechanisms in B. anthracis are inefficient compared with those found in B. subtilis (Cote et al, 2018). Therefore, strains with non-specific cleavage might not survive in the absence of homologous arms to repair the genomic DNA breaks.…”
Section: Discussionmentioning
confidence: 99%
“…Sporulation and subsequent spore purification of B. anthracis and other Bacilli was done as previously described [ 33 ] with slight modifications. A colony of a fresh overnight culture of B. anthracis (or other Bacilli) was used to inoculate 50 mL sporulation medium containing 0.8% nutrient broth (Merck KGaA) amended with 0.05 mM MnCl 2 , 0.7 mM CaCl 2 and 1.0 mM MgCl 2 [ 34 ] in 500 mL baffled flasks.…”
Section: Methodsmentioning
confidence: 99%